Research on the influencing factors of users’ continuance intentions of wearable medical devices—a perspective integrating the UTAUT model and gamification elements - Yulin Tian; Zoumin Li; Dong Liu; Sangbum Son (Frontiers in Public Health)
With the global aging population and the increasing prevalence of chronic diseases, the application of wearable medical devices in health management has garnered widespread attention. However, despite the significant advantages of these devices in health monitoring and disease prevention, many users discontinue their use within a short period, posing challenges to their long-term adoption. This study develops a research framework by combining the Unified Theory of Acceptance and Use of Technology (UTAUT) model with gamification components to methodically examine the critical factors influencing users’ sustained intention to use wearable medical devices (WMD). A survey method was employed, collecting 362 valid responses, and applied structural equation modeling (SEM) for empirical analysis. Results demonstrate that performance expectancy, effort expectancy, social influence, and gamification elements all exert a significant positive effect on users’ continued usage intention. The results contribute to the theoretical foundation for improving the design and market promotion of WMD and offer actionable recommendations for developers and policymakers to boost user adoption.